Three-Dimensional Architecture of Glomerular Endothelial Cells Revealed by FIB-SEM Tomography - Kawasaki, Yuto; Hosoyamada, Yasue; Miyaki, Takayuki; Yamaguchi, Junji; Kakuta, Soichiro; Sakai, Tatsuo; Ichimura, Koichiro (Frontiers in Cell and Developmental Biology, 2021)
Focused-ion beam-scanning electron microscopic (FIB-SEM) tomography enables easier acquisition of a series of ultrastructural, sectional images directly from resin-embedded biological samples. In this study, to clarify the three-dimensional (3D) architecture of glomerular endothelial cells (GEnCs) in adult rats, we manually extracted GEnCs from serial FIB-SEM images and reconstructed them on an Amira reconstruction software. The luminal and basal surface structures were clearly visualized in the reconstructed GEnCs, although only the luminal surface structures could be observed by conventional SEM. The luminal surface visualized via the reconstructed GEnCs was quite similar to that observed through conventional SEM, indicating that 3D reconstruction could be performed with high accuracy. Thus, we successfully described the 3D architecture of normal GEnCs in adult rats more clearly and precisely than ever before. The GEnCs were found to consist of three major subcellular compartments, namely the cell body, cytoplasmic ridges, and sieve plates, in addition to two associated subcellular compartments, namely the globular protrusions and reticular porous structures. Furthermore, most individual GEnCs made up a “seamless” tubular shape, and some of them formed an autocellular junction to make up a tubular shape. FIB-SEM tomography with reconstruction is a powerful approach to better understand the 3D architecture of GEnCs. Moreover, the morphological information revealed in this study will be valuable for the 3D pathologic evaluation of GEnCs in animal and human glomerular diseases and the structural analysis of developmental processes in the glomerular capillary system.